Impact of familiar cues on reading comprehension: an investigative study of Pakistani English language learners - Aqdas, Shayan (Frontiers in Education, 2025)
Language development is influenced by a number of factors, one of them is existing knowledge. Previous studies suggest that contextualizing language learning materials can help low-skilled learners improve their performance. This study is grounded in Frederic Bartlett’s schema theory (1932), which posits that individuals use prior knowledge to interact with new information. A sample of 60 students was divided into an experimental group (EG) and a control group (CG), with 30 students in each. Both groups read an excerpt from The Secret Garden by Frances Hodgson Burnett, but the experimental group received instruction that included familiar cultural cues to aid comprehension. The groups were assessed through comprehension questions, which were evaluated based on vocabulary, evaluation, and inferential skills. A post-assessment survey using a Likert scale examined students’ perceptions of the contextualization’s impact on their performance. The results indicated that students performed better when academic content was familiar. The experimental group demonstrated stronger analytical and inferential skills, displaying the benefits of using culturally relevant cues to improve comprehension and engagement. This study supports the previous findings and emphasizes the value of contextualized learning to enhance students’ interest and comprehension.